The Interpretation of Misconduct Act as A Reason to Dismiss President: An Ethical Approach - Antari, Putu Eva Ditayani (De Jure: Jurnal Hukum dan Syari'ah, 2021)
Abstract: The President of Indonesia gets the supervision of the Senate as regulated by the constitution. The Senate has the authority to dismiss the president at the recommendation of the House of Representatives if the president is deemed to have committed treason against the state, corruption or bribery, serious crimes, and misconduct acts or is deemed no longer eligible for president. Misconduct act is a reason for dismissing a president does not have legal certainty because the constitution does not limit the intent of the misconduct act itself. At the same time, the Constitutional Court Act in Indonesia has extended the meaning of this misconduct act. This paper will discuss the meaning of the misconduct act from an ethical perspective and comparative study. Furthermore, it also describes the appropriateness of the limits on misconduct as regulated in the Constitutional Court Act with the intention of constitution drafting for amendment. These legal problems will then be studied using normative methods through historical, comparative, and interpretation approaches then presented on a descriptively-analysis paper. The results of the study indicate that a misconduct act is an act that degrades the dignity of the position as president. Misconduct acts have a broader meaning than criminal acts but can also violate unwritten norms that are determined as law in society.Keywords: dismissal of president; interpretation; misconduct act.Abstrak: Presiden Indonesia mendapat pengawasan dari Senat sebagaimana diatur dalam konstitusi. Senat memiliki kewenangan untuk memberhentikan presiden atas rekomendasi DPR jika presiden dianggap telah melakukan pengkhianatan terhadap negara, korupsi atau penyuapan, kejahatan berat, dan tindakan tidak senonoh atau dianggap tidak lagi memenuhi syarat untuk menjadi presiden. Perbuatan tercela menjadi alasan memberhentikan seorang presiden yang tidak memiliki kepastian hukum, karena konstitusi tidak membatasi maksud dari perbuatan tercelaitu sendiri. Padahal UU MK di Indonesia telah memperluas makna dari maksud perbuatan maksiat ini. Makalah ini akan membahas tentang pengertian perbuatan salah dari sudut pandang etika. Lebih lanjut, juga menggambarkan kesesuaian batasan perbuatan tercela sebagaimana diatur dalam UU MK dengan maksud penyusunan konstitusi untuk diubah. Permasalahan hukum tersebut kemudian akan dikaji dengan menggunakan metode normatif melalui pendekatan historis, komparatif, dan interpretasi, kemudian disajikan dalam makalah analisis deskriptif. Hasil penelitian menunjukkan bahwa perbuatan tercela merupakan perbuatan yang merendahkan martabat jabatan sebagai presiden. Perbuatan tercela memiliki makna yang lebihÂ  luas dari tindak pidana, namun bisa juga pelanggaran atas norma-norma tak tertulis yang berlaku sebagai hukum di masyarakat.Kata Kunci: Interpretasi, pemberhentian presiden; perbuatan tercela.